Desmoid tumor mimics local recurrence of extremity sarcoma on MRI. Issue 8 (24th March 2020) - Sabharwal, Samir; Ahlawat, Shivani; Levin, Adam S.; Meyer, Christian F.; Brooks, Eugene; Ligon, John; Morris, Carol D.
Abstract: Background and Objectives: The development of desmoid fibromatosis after tumor resection may mimic local recurrence. To our knowledge, this phenomenon has not been reported after extremity sarcoma resection. We report four cases of desmoid‐type fibromatosis ("desmoid tumors") mimicking local recurrence after extremity sarcoma resection. Methods: We retrospectively reviewed the records of patients treated for extremity sarcoma by our orthopedic oncology service from 2014 to 2019 and identified four patients with biopsy‐proven desmoid tumors. We extracted clinical, pathologic, radiographic, and operative data for the primary neoplasms and desmoid tumors. Results: Four patients with postresection surveillance magnetic resonance imaging suspicious for local recurrence underwent further analysis showing desmoid tumors. Patients underwent image‐guided needle biopsy, with specimens demonstrating fibromatosis‐type histologic characteristics. Two cases were β‐catenin positive. Desmoid tumors were managed with observation. No patient had experienced local or distant recurrence of the primary tumor at a mean follow‐up of 30 months after resection (range, 23‐34 months); none underwent surgery for symptoms of desmoid tumors. Conclusions: Desmoid tumors should be considered part of the differential diagnosis when assessing patients with radiographic concern for postresection local recurrence of extremity bone and soft‐tissue sarcoma. An image‐guided needle biopsy can inform diagnosis and management.